Demographic and clinical properties of juvenile-onset Behcet's disease: A controlled multicenter study - Karincaoglu, Yelda; Borlu, Murat; Toker, Sernra Cikman; Akman, Ayse; Onder, Meltem; Gunasti, Suhan; Alpsoy, Erkan (Mosby-Elsevier, 2008)
Background: Behcet's disease (BD) is a multisystemic inflammatory disorder Of unknown origin. The disease usually occurs between the second and the fourth decades, whereas it is uncommon in children. Objective. In this multicenter study, we aimed to describe the demographic and clinical features along with severity in juvenile- versus adult-onset 131). Methods: Patients with initial symptoms at age 16 years or younger were considered as having juvenileonset 131). In all, 83 patients with juvenile-onset BID (38 male and 45 female; mean age 19.6 +/- 7.6 years) and 536 with adult-onset (>16 years) BD (293 male and 243 female; mean age 39.2 +/- 10.1 years) who fulfilled the classification criteria of the International Study Group for BD were involved in the study. Results: Familial cases were more frequent in juvenile-onset compared with adult-onset BD (19% vs 10.3%; P=.017). The mean age of disease onset was 12.29 +/- 3.54 years in juvenile-onset 131) and 31.66 +/- 8.71 years in adult-onset 131). Mucocutaneous lesions and articular symptoms were the most commonly observed manifestations in both groups. The frequency of disease manifestations was not different between juvenile and adult-onset BID, except neurologic and gastrointestinal involvement, which were higher in juvenileonset 131) than adult-onset BD (P =.027 and P =.024, respectively). Oral ulcer was the most common onset manifestation of both juvenile-onset (86.74%) and adult-onset (89-55%) BD. The frequencies of onset manifestations of 131) were similar, except genital ulcer, which was higher in adult-onset 131) (P =.025). Limitations: Our study consisted of patients with 131) mainly applying to dermatology and venerology departments. Therefore, it can be speculated that this Study includes rather a milder spectrum of the disease. Conclusions: Although the clinical spectrum of juvenile-onset BD seems to be similar to adult-onset BD, the frequency of severe organ involvement was higher. Because of the higher prevalence of familial cases in juvenile-onset BD, it can be speculated that genetic factors may favor early expression of the disease with severe organ involvement.
Keywords: Features; Children; Etiology